ОСОБЕННОСТИ АДМИНИСТРАТИВНЫХ ОТНОШЕНИЙ, КОТОРЫЕ ВОЗНИКАЮТ В ДЕЯТЕЛЬНОСТИ ХОЗЯЙСТВЕННЫХ СУДОВ УКРАИНЫ ПРИ ВЗАИМОДЕЙСТВИИ С ДРУГИМИ СУБЪЕКТАМИ - Белинская, Ярослава Юрьевна (SUPREMANCE OF LAW, 2017)
In the article, on the basis of theoretical definitions of the concept of legal relations, administrative relations, the author defines his own concept of administrative relations that arise in the activities of economic courts when interacting with other entities. The author also determined the features of such relations, the reasons for their occurrence and the types.
Keywords: legal relations; administrative relations; economic court; public authorities; mechanism of administrative and legal influence